2017
DOI: 10.1080/14647273.2017.1287433
|View full text |Cite
|
Sign up to set email alerts
|

Double ovarian stimulation (DuoStim) protocol for fertility preservation in female oncology patients

Abstract: This article describes a revised ovarian stimulation protocol (DuoStim) for fertility preservation in female oncology patients which aims to maximise the number of gametes obtained with subsequent improvement in cumulative birth rate, without delaying cancer treatment. Ten patients diagnosed with malignancy between September 2014 and October 2015 were included. The patients were treated with the DuoStim protocol, undergoing two consecutive ovarian stimulation cycles and two oocyte retrievals. The primary outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 38 publications
0
47
0
1
Order By: Relevance
“…However, in many patients, there are not enough oocytes collected to ensure reasonably good chances of pregnancy. Based on this, when the time is limited and the oocytes collected from one stimulation are insufficient, DuoStim protocols might be discussed with the oncologist together with the patients as a valuable option for fertility preservation (23)(24)(25)(26).…”
Section: When Is Duostim Indicated?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in many patients, there are not enough oocytes collected to ensure reasonably good chances of pregnancy. Based on this, when the time is limited and the oocytes collected from one stimulation are insufficient, DuoStim protocols might be discussed with the oncologist together with the patients as a valuable option for fertility preservation (23)(24)(25)(26).…”
Section: When Is Duostim Indicated?mentioning
confidence: 99%
“…A further pilot study published in 2017 by Tsampras et al (23) tested the efficacy of double stimulation for fertility preservation in oncological patients. Ten patients underwent double stimulation with GnRH antagonist and HMG protocol.…”
Section: Updated Body Of Evidence Regarding the Clinical Implementatimentioning
confidence: 99%
“…Based on the concept of multiple follicular waves, a second cycle can be proposed following the first one, offering the possibility of accumulating vitrified oocytes (36). Double ovarian stimulation (DuoStim) has been performed with success in cancer patients, leading to the vitrification of around 16 oocytes per patient (range: 6-32; n=10) (37).…”
Section: Efficiency and Outcomes Of Oocyte Cryopreservationmentioning
confidence: 99%
“…The impact of the disease on the ovarian response remains controversial. Several studies have not shown any difference in the number of oocytes collected between oncological and nononcological patients or according to disease type (26,(37)(38)(39)(40). Others have reported lower fertility preservation performance in patients with breast cancer (29) and BRCA-mutated breast cancer (41), lymphoma (42) and ovarian cancer (39).…”
Section: Impacts Of the Disease On Efficiencymentioning
confidence: 99%
“…If a suitable follicular development wave is achieved thanks to this process, random ovulation induction forms can be implemented as a late follicular and luteal ovulation induction in the same cycle except for the classical ovulation induction. Depending on the same principle, more than one ovulation induction in both follicular and luteal phases can be carried out in the same cycle [31,32].…”
Section: Aromatase Inhibitorsmentioning
confidence: 99%